Pengaruh pajak dearah, retribusi daerah, laba Badan Usaha Milik Daerah (BUMD), dan belanja modal terhadap Pendapatan Asli Daerah (PAD) - Tiwi Mei Listyowati; Anim Rahmayati (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
The purpose of this study is to determine the effect of local taxes, regional levies, profits of regionally owned enterprises, and capital expenditures on regional original income in district/city governments in Central Java Province in 2019-2021. The sampling technique uses nonprobability sampling. The sample used was 35 district and city governments in Central Java Province with 105 data. The data analysis technique used in this study is panel data regression. This type of research is quantitative research. The variables in this study are Local Own Revenue, Regional Retribution, BUMD Profits, and Capital Expenditures. The data used is secondary data with data collection techniques using documentation. The result of the study shows that local taxes have a positive effect on regional original income. Regional levies do not affect local revenue. Profits from regionally owned enterprises have a positive effect on local revenue. Capital expenditure has a negative effect on local revenue